If x = 0, simplify the expression completely.
![If x 0 simplify the expression completely class=](https://us-static.z-dn.net/files/d12/79d1b2e274ef420f7680dda9275b7919.png)
Answer:
You have to apply Indices Law :
[tex] {a}^{m} \div {a}^{n} ⇒ {a}^{m - n} [/tex]
So for this question :
[tex] \frac{ \sqrt[3]{x} }{ {x}^{ \frac{1}{8} } } [/tex]
[tex] = \sqrt[3]{x} \div {x}^{ \frac{1}{8} } [/tex]
[tex] = {x}^{ \frac{1}{3} } \div {x}^{ \frac{1}{8} } [/tex]
[tex] = {x}^{ \frac{1}{3} - \frac{1}{8} } [/tex]
[tex] = {x}^{ \frac{5}{24} } [/tex]